Model Bisnis Inovatif dalam Sektor Peternakan untuk Mendukung Pembangunan Berkelanjutan : Innovative Business Models in the Livestock Sector to Support Sustainable Development - Azis, Arif Rahman Azis; Woki Bilyaro; Muhammad Dani; Nurazizah Ramadhanti; Rizky Amrullah Chaniago; Akbar Abdurrahman Mahfudz; Muhammad Subhan Hamka; Kade Wahyu Saputri (Buletin Peternakan Tropis, 2025)
Innovative business models are critical for addressing the complex sustainability challenges within the livestock sector. This systematic review analyzes various innovative business models designed to align livestock production with the principles of sustainable development. The models examined include the circular economy, Integrated Crop-Livestock Systems (ICLS), Precision Livestock Farming (PLF), digitally-enabled value chains (blockchain and e-commerce), and modern cooperatives. The analysis reveals that these models contribute significantly to the three pillars of sustainability—economic, social, and environmental. They achieve this by transforming waste into valuable resources, enhancing resource efficiency, improving productivity and animal welfare, and empowering smallholder farmers. The key finding is that no single model offers a universal solution; instead, the future of sustainable livestock production lies in integrated, context-specific approaches that combine technological innovation with inclusive social structures. This review concludes by emphasizing the need for policies and investments that support the adoption of these hybrid models to build a livestock sector that is productive, equitable, and environmentally responsible